137k views
2 votes
Can someone pls do 25 and 26 with working

Can someone pls do 25 and 26 with working-example-1

1 Answer

4 votes

25.

Show


(\tan x + \sin x)/(\tan x - \sin x) = (\sec x + 1)/(\sec x - 1)


(\tan x + \sin x)/(\tan x - \sin x)


= ((\sin x)/(\cos x) + \sin x)/((\sin x)/(\cos x) - \sin x)


= (\sin x ( (1)/(\cos x) + 1))/(\sin x( ( 1)/(\cos x) - 1))


= (\sec x + 1)/(\sec x - 1) \quad\checkmark

26.

Show


(\cot \theta + \csc \theta - 1)/(\cot \theta - \csc \theta +1) = (1+\cos \theta)/(\sin \theta)

That's the cotangent half angle formula on the right, so I guess on the left too.

I fooled around with this one for a while before I took the hint which was to let
\theta=2x.


(\cot 2x + \csc 2x - 1)/(\cot 2x- \csc 2x +1)


=( (\cos 2x / \sin 2x) + (1/\sin 2x ) - 1)/(\cos 2x/\sin 2x - 1/\sin 2x + 1)


=(\cos 2x + 1 - \sin 2x)/(\cos2x - 1 + \sin 2x)


=(2\cos^2 x - 1 + 1 -2 \cos x \sin x )/(1 - 2\sin^2x-1 + 2\sin x \cos x)


=(2 \cos^2 x -2 \cos x \sin x )/(-2\sin^2x+2 \sin x \cos x)


=(2\cos x)/(2 \sin x) \cdot (\cos x- \sin x)/(-\sin x +\cos x)


=(2\cos x)/(2\sin x)


=(2\cos^2 x)/(2\sin x\cos x)


=(1 + 2\cos^2 x - 1)/(2\sin x\cos x)


= (1 + \cos 2x)/(\sin 2x)


=(1+\cos \theta)/(\sin \theta) \quad\checkmark

------

For another answer, let's use the hint on this one, which was to write


1=\csc^2 \theta - \cot^2 \theta

That's a good hint; first let's verify if it's true.


\sin^2 \theta + \cos^2 \theta = 1


\sin^2 \theta = 1 - \cos^2 \theta


1 = (1)/(\sin ^2 \theta) - (\cos ^2 \theta)/(\sin ^2 \theta)


1 = \csc^2 \theta - \cot^2 \theta \quad\checkmark

Now,


(\cot \theta + \csc \theta - 1)/(\cot \theta - \csc \theta +1)


= (\cot \theta + \csc \theta - (\csc^2 \theta - \cot^2 \theta))/(\cot \theta - \csc \theta +1)


= (\cot \theta + \csc \theta +(\cot^2 \theta - \csc^2 \theta))/(\cot \theta - \csc \theta +1)


= (\cot \theta + \csc \theta +(\cot \theta - \csc \theta)(\cot \theta + \csc \theta))/(\cot \theta - \csc \theta +1)


= ((\cot \theta + \csc \theta)(1+ \cot \theta - \csc \theta))/(\cot \theta - \csc \theta +1)


=\cot \theta + \csc \theta


=( \cos \theta)/(\sin \theta)+ (1)/(\sin \theta)


=(1+ \cos \theta)/(\sin \theta) \quad\checkmark

User Xunzhang
by
6.3k points